Menelusuri Keberhasilan dan Kendala Pemda di Provinsi Jawa Barat dalam Upaya Memperoleh Opini WTP dari BPK: Studi Kasus Pemerintah Daerah Kabupaten/Kota di Provinsi Jawa Barat: Kata Kunci: Keberhasilan, Kendala, Pengelolaan Keuangan, dan Opini Audit - Puji Astuti Rahayu; Sylvia Fettry; Monica Paramita (Universitas Kristen Maranatha, 2020)
Financial management reforms to improve quality are continuously carried out. Regional financial management is carried out in an integrated system embodied in the Local Government Budget which is determined annually by regional regulations. The drafting of the Local Government Budget is guided by the Local Government Work in order to realize services to the community to achieve the goal of the state. It requires an inflow of funds to finance regional expenditure. Regional sources of revenue can be obtained from three sources: a) local own-source revenue, b) fiscal balance transfers from the central government to regions, c) other local own-source revenue. As a form of transparent and accountable regional financial management, it is necessary to prepare financial reports audited by the BPK. Based on the result of the audit, the local government experienced improvement and decreased Opinion on The Report On Local Government Finance from 2013 to 206. The opinion that has been achieved are an illustration of the success in the presenting of the financial statement and the constraints faced by the Regional Government in West Java Province in obtaining WTP Opinions from BPK. This research is descriptive, and data collection techniques are questionnaires, the study of literature from Report of Audit Findings and interviews with related parties